139 Improving road traffic safety through legislations: an empirical evaluation of the 2004 chinese road traffic law. (1st September 2016) - Li, Qingfeng; He, Huan; Bishai, David M; Hyder, Adnan A
Abstract : Background: Road traffic injuries (RTI) impose a heavy burden in many developing counties. Among other interventions, legislations have been proposed in some countries, such as China where the first road traffic law was passed in 2004. We evaluated the impact of this law on reducing RTI. Methods: Multiple linear regression models at both country and province level, as well as a longitudinal regression model at province level were applied with the data collected during 1996–2012. Using the Chow tests, we identified structure changes in the trend of traffic fatalities in China as a whole and in most provinces around 2004. As sensitivity analyses, the estimations were replicated in two other hypothetical scenarios, assuming a flat trajectory (per data from Disease Surveilannce Points system) and a increasing trajectory (per data from Ministry of Health's vital registion system) since 2004. Results: We estimated that during 2005–2012, about 498.550 (95% uncertainty interval 408.943–588.157) deaths, 4.060.591 (95% uncertainty interval 2.960.588–5.160.594) injuries and 5.658.494 (95% uncertainty interval 3.783.098–7.533.890) crashes have been averted due to the implementatoin of the 2004 traffic law. The health benefits of the legislation remained tremendous even after adjusted for the possible underreporting problem in the traffic fatality data. Conclusions: Our study suggests that other developing countries can learn from the success of the 2004 Chinese traffic safety law and improve road traffic safety by introducing effective legislations.